Ozone-Induced Oxidative Stress, Neutrophilic Airway Inflammation, and Glucocorticoid Resistance in Asthma - Enweasor, Chioma; Flayer, Cameron H.; Haczku, Angela (Frontiers in Immunology, 2021)
Despite recent advances in using biologicals that target Th2 pathways, glucocorticoids form the mainstay of asthma treatment. Asthma morbidity and mortality remain high due to the wide variability of treatment responsiveness and complex clinical phenotypes driven by distinct underlying mechanisms. Emerging evidence suggests that inhalation of the toxic air pollutant, ozone, worsens asthma by impairing glucocorticoid responsiveness. This review discusses the role of oxidative stress in glucocorticoid resistance in asthma. The underlying mechanisms point to a central role of oxidative stress pathways. The primary data source for this review consisted of peer-reviewed publications on the role of ozone in airway inflammation and glucocorticoid responsiveness, indexed in PubMed. Our main search strategy focused on cross-referencing “asthma and glucocorticoid resistance” against “ozone, oxidative stress, alarmins, innate lymphoid, NK and γδ T cells, dendritic cells and alveolar type II epithelial cells, glucocorticoid receptor and transcription factors”. Recent work was placed in the context from articles in the last 10 years and older seminal research papers and comprehensive reviews. We excluded papers that did not focus on respiratory injury in the setting of oxidative stress. The pathways discussed here have however wide clinical implications to pathologies associated with inflammation and oxidative stress and in which glucocorticoid treatment is essential.